2019
DOI: 10.3390/f10110935
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges of the Forestry Sector Communication Based on an Analysis of Research Studies in the Czech Republic

Abstract: Achieving public support and understanding in addressing the challenges of climate change and the bark beetle calamity is a prerequisite for the successful future of Czech forestry. The most important instrument for achieving public support is communication. To be effective, this communication has to be built on a communication strategy reflecting the long-term goals of forest policy and has to be based on both current analyses and other relevant information, which, in turn, is based on the research results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Largely, the public relatively weakly perceived the image of the SFE. Comparable results were provided by Riedl et al (2019) and Krejčí et al (2019) where the public is aware of the declining balance of forests stands in the Czech Republic. In Germany, Sweden and Czech Republic, the public sensibly takes notice of environmental problems in forests such as pollution and climate change (Ranacher et al 2020).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Largely, the public relatively weakly perceived the image of the SFE. Comparable results were provided by Riedl et al (2019) and Krejčí et al (2019) where the public is aware of the declining balance of forests stands in the Czech Republic. In Germany, Sweden and Czech Republic, the public sensibly takes notice of environmental problems in forests such as pollution and climate change (Ranacher et al 2020).…”
Section: Discussionmentioning
confidence: 95%
“…As Lichý (2013) suggested, SFE's communication with media should be long-term and in cooperation with mainstream media on a regional and national level with all stakeholders (public, experts, NGOs). The longterm character and consistency of the communication with media was also highlighted by Riedl et al (2019). Moreover, the communication of SFE should be proactive (Baerlocher 2020).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…For instance, Michal et al [18] indicated that knowledge by consumers and interested parties is key to the effectiveness of forest certification, so that it can be a real means of achieving sustainability. In this vein, communication should be performed to share information with stakeholders using long-term strategies aimed at consistency [19].…”
Section: Description Of Respondents Reasons To Adhere and Satisfactionmentioning
confidence: 99%